English Language Teaching Educational Change: A Retrospective Analysis of Teacher Professional Development - Le Xuan Mai; Le Thanh Thao (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
The importance of English has demanded the introduction of English language teaching (ELT) educational reforms (ERs) in the Vietnamese context. However, the results of these reforms did not satisfy Vietnamese educators; as a result, many studies have explored the related issues, but almost none of them emphasized English as a foreign language (EFL) teachers’ perceptions of the necessities of the reforms. Accordingly, this current study was conducted to fill in the aforementioned gap. Driven by that emphasis, this qualitative study used semi-structured interviews as a data-collecting instrument. Regarding the studied sampling, six EFL high school teachers from Southwest Vietnam were recruited as the interviewees. According to the findings of the present study, teachers in Vietnam strongly perceived the need for ELT ERs. Besides, the reforms were fundamental to help catch up with the era of globalization. At the conclusion of the paper, some discussions focusing primarily on teacher training issues and educational implications, as well as suggestions for future research, were presented.